A systematic literature review on environmental, agronomic, and socioeconomic factors for the integration of small-scale coffee producers into specialized markets in Oaxaca, Mexico - Aragón-Guzmán, Sheila Estefanía; Regino-Maldonado, Juan; Vásquez-López, Alfonso; Toledo-López, Arcelia; Nuria Jurado-Celis, Silvia; Granados-Echegoyen, Carlos Alejandro; Landero-Valenzuela, Nadia; Arroyo-Balán, Fabián; Quiroz-González, Beatriz; Peñaloza-Ramírez, Juan M. (Frontiers in Sustainable Food Systems, 2024)
The coffee sector's challenges, such as low and volatile prices, prompt adopting strategies focused on product differentiation, including high-quality specialty coffee. Nevertheless, documented evidence shows that small producers in Oaxaca, Mexico, are not equally benefiting from this market opportunity compared to other states in Mexico, such as Veracruz or Chiapas. This review article identifies and analyzes the factors in integrating small Oaxacan producers into the specialty market. A total of 138 scientific contributions were analyzed, emphasizing three thematic axes: 1) Trends and behavior of the coffee market. 2) Factors to enable the production of high-quality coffee and 3) Current situation and challenges of small coffee producers in the specialized market. We found that coffee quality depends on the environment (mainly altitude, temperature, and geographical conditions) and agronomic, genetic, and socio-economic factors. Moreover, agronomic and genetic factors should focus on choosing coffee varieties suited to the environmental conditions of the farm and adopting innovations in production, harvest, and post-harvest processes. The most significant socio-economic factors that hinder small coffee producers' participation in the specialized market include but are not limited to, lack of information, social connection, and financial resources. However, in the literature analyzed here, it was also possible to identify specific farmworker experiences that operate with a community approach and have inserted their small producers into high-quality market transactions. For this reason, this article suggests that the standardization model of quality from the collective approach within the community-based enterprise is a sustainable and inclusive alternative to achieve the goal: the insertion of small Oaxacan coffee producers into the more significant specialty market.